Godard mon amour [videorecording (DVD)] - Hazanavicius, Michel; Hazanavicius, Michel; Hazanavicius, Michel; Garrel, Louis; Martin, Stacy, 1991-; Bejo, Bérénice, 1976-; Wiazemsky, Anne (Contemporary classics (Cohen Media Group), 2018)
Follows the affair in the 1960s of French filmmaker Jean-Luc Godard with Anne Wiazemsky, a seventeen-year-old actress in one of his films.